Inhibition of insulin/IGF‐1 receptor signaling protects from mitochondria‐mediated kidney failure - Christina Ising; Sybille Koehler; Sebastian Brähler; Carsten Merkwirth; Martin Höhne; Olivier R Baris; Henning Hagmann; Martin Kann; Francesca Fabretti; Claudia Dafinger; Wilhelm Bloch; Bernhard Schermer; et al. (EMBO Molecular Medicine)
Abstract Mitochondrial dysfunction and alterations in energy metabolism have been implicated in a variety of human diseases. Mitochondrial fusion is essential for maintenance of mitochondrial function and requires the prohibitin ring complex subunit prohibitin‐2 (PHB2) at the mitochondrial inner membrane. Here, we provide a link between PHB2 deficiency and hyperactive insulin/IGF‐1 signaling. Deletion of PHB2 in podocytes of mice, terminally differentiated cells at the kidney filtration barrier, caused progressive proteinuria, kidney failure, and death of the animals and resulted in hyperphosphorylation of S6 ribosomal protein (S6RP), a known mediator of the mTOR signaling pathway. Inhibition of the insulin/IGF‐1 signaling system through genetic deletion of the insulin receptor alone or in combination with the IGF‐1 receptor or treatment with rapamycin prevented hyperphosphorylation of S6RP without affecting the mitochondrial structural defect, alleviated renal disease, and delayed the onset of kidney failure in PHB2‐deficient animals. Evidently, perturbation of insulin/IGF‐1 receptor signaling contributes to tissue damage in mitochondrial disease, which may allow therapeutic intervention against a wide spectrum of diseases.